Reasons assigned to suicide attempts: adolescents' perceptions - Émilen Vieira Simões; Adriane Maria Netto de Oliveira; Leandro Barbosa de Pinho; Luciano Garcia Lourenção; Stella Minasi de Oliveira; Francisca Lucélia Ribeiro de Farias (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objective: identify the reasons for attempting suicide from the perspective of adolescents. Methods: qualitative study conducted with ten adolescents who attempted suicide and were attending a Centro de Atenção Psicossocial Infanto-Juvenil located in a city in the south of Brazil. Semi-structured interviews were held in July 2020 using WhatsApp. Data were analyzed according to Minayo's Content Thematic Analysis. Results: the adolescents' reports listed the reasons that triggered suicide attempts, such as changes in the adolescents' life cycle and violence, which led them to attempt suicide to solve problems. Final considerations: Data analysis revealed the reasons that triggered suicide attempts from the adolescents' perspective and difficulties to cope with problems, probably explained by their lack of experience in dealing with frustrations and disappointments.